Literature Study: Building Superior Human Resources Through Digital Learning in the Modern Education Era - Dhiwanti Puspa Putih Wardani; Ida Rindaningsih (Aslim: Journal of Education and Islamic Studies, 2025)
In the era of modern education marked by advances in information and communication technology, digital learning has become one of the main solutions in building superior human resources (HR). This article examines the role of digital learning in improving the quality of education and developing students' skills that are relevant to the demands of the world of work. Through a case study analysis approach and literature review, this study identifies various effective digital learning methods and platforms, as well as the challenges faced in their implementation, such as the gap in technology access and educator readiness. The results of the study indicate that digital learning not only increases student engagement and motivation, but also enables the development of critical and creative skills needed to compete in the global era. In addition, this article provides recommendations for stakeholders in education to optimize the use of technology in the curriculum, as well as create an educational ecosystem that supports the development of quality HR. Thus, digital learning is expected to contribute significantly to creating a generation that is ready to face future challenges.